2022
DOI: 10.1002/eco.2408
|View full text |Cite
|
Sign up to set email alerts
|

Riparian forest productivity decline initiated by streamflow diversion then amplified by atmospheric drought 40 years later

Abstract: Riparian trees and their annual growth rings can be used to reconstruct drought histories related to streamflow. Because the death of individual trees reduces competition for survivors, however, tree-ring chronologies based only on surviving trees may underestimate drought impacts. This problem can be addressed by calculating productivity at the stand scale to account for tree mortality and establishment. In the semi-arid Great Basin in the western United States, we calculated riparian wood production from 194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…The frequency and intensity of hot droughts in the western United States is increasing due to climate warming, which can negatively impact river hydrology and riparian ecosystems (Perry et al, 2012; Schook et al, 2022; Williams et al, 2022). Low precipitation during droughts reduces plant productivity, with hot droughts adding an additional stressor in the form of higher vapor pressure deficit (VPD) that amplifies plant stress and exacerbates declines in gross primary productivity (GPP) (Dannenberg et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency and intensity of hot droughts in the western United States is increasing due to climate warming, which can negatively impact river hydrology and riparian ecosystems (Perry et al, 2012; Schook et al, 2022; Williams et al, 2022). Low precipitation during droughts reduces plant productivity, with hot droughts adding an additional stressor in the form of higher vapor pressure deficit (VPD) that amplifies plant stress and exacerbates declines in gross primary productivity (GPP) (Dannenberg et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We expanded the interpretations of aerial photographs, undertook field observations and analysed the historical river flow patterns to consider the likely causes of the cottonwood mortality. The prior analyses indicated that declining river flows contributed (Rood et al, 1995; Rood & Heinze‐Milne, 1989), and we sought to resolve the influences from river regulation and water withdrawal versus impacts from climate variation and change (Andersen, 2016; Cooper et al, 1999; Schook et al, 2022). Since riparian cottonwoods are highly sensitive to natural or anthropogenic variations in river flow (Schook et al, 2020; Stromberg & Patten, 1992; Williams & Cooper, 2005; Zimmerman et al, 2022), we commenced the study with two hypotheses:Hypothesis Due to the progressive increase in water withdrawal over the Twentieth Century, cottonwood abundances would progressively decline along the St. Mary River.…”
Section: Introductionmentioning
confidence: 99%
“…Water development generally reduces peak streamflows, resulting in slower rates of channel migration on meandering rivers, and less flood deposition on valley‐constrained rivers, which leads to reduced regeneration of disturbance‐dependent Populus‐Salix forests (Friedman et al, 1997, Scott et al 1996). Water development can also reduce riparian groundwater levels and/or growing season flows, diminishing Populus growth and survival (Rood et al, 2003; Schook et al, 2022; Williams et al, 2022). In the last half century, these factors have exacerbated the effects of climatic drought, resulting in cottonwood decline on many large rivers, for example, the Arkansas River (Snyder & Miller, 1991), Rio Grande (Howe & Knopf, 1991), lower Colorado River (Nagler et al, 2020), and the Santa Clara River (Williams et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, even on perennial rivers cottonwood transpiration and growth can be limited by water availability, especially in late summer when groundwater levels may decline, soil moisture is depleted, and warm and dry weather increases water demand (Phelan et al, 2022; Williams et al, 2022). Previous studies on other semi‐arid region rivers have documented relationships between Populus annual growth and climate (e.g., precipitation) or hydrology (e.g., streamflow, soil moisture), relationships which can be altered by water development (Edmondson et al, 2014; Friedman et al, 2018; Reily & Johnson, 1982; Schook et al, 2022). However, no such studies have been conducted on the South Platte River, where cottonwood forests appear to be faring better than on other managed semi‐arid rivers.…”
Section: Introductionmentioning
confidence: 99%